Respuesta :

debmc7
Ok. We have

-6x + 8y = 18

They also tell us
3x = y, which is also y = 3x (just reversed)

So we take 3x and substitute it where we see y in the first equation, then solve for x

-6x + 8(3x) = 18
-6x + 24x = 18
18x = 18
x = 1

Then we solve for y
y = 3x
y = 3(1)
y = 3

Hope this helps. LMK if you have questions.

9514 1404 393

Answer:

  (x, y) = (-1, -3)

Step-by-step explanation:

You notice that the coefficient of x in the first equation is double the opposite of the coefficient of x in the second equation. This means we can make the x-term disappear by adding twice the second equation to the first.

  (-6x +8y) +2(3x) = (-18) +2(y)

  8y = -18 +2y . . . simplify

  6y = -18 . . . . . . . subtract 2y

  y = -3 . . . . . . . . . divide by 6

Substituting into the second equation, we have ...

  3x = -3

  x = -1 . . . . . . . . . divide by 3

The solution is (x, y) = (-1, -3).